Studies on flow from converging nozzle and the effect of nozzle pressure ratio for area ratio of 6.25 - Ashfaq, Syed; Khan, Sher Afghan (International Journal of Engineering Science & Advanced Technology, 2014)
Micro jets are used in the present experimental study as an active control. Flow from converging nozzle to suddenly expanded circular duct of larger cross-sectional area than that of nozzle exit area were studied experimentally, focusing attention on the base pressure and the flow development in the duct. Mach number and nozzle pressure ratio are considered as the flow parameters. The geometrical parameters considered are the area ratio of the sudden expansion duct cross-section area to the nozzle exit area and the length to diameter ratio of the duct. To find the effect of micro jets as an active control on base pressure as well as on the flow field developed in the duct, the micro jets of 1 mm orifice diameter are used. They are located at 900 intervals along a pitch circle diameter 1.3 times the nozzle exit diameter. In this study, the area ratio considered is 6.25. The flow parameter, nozzle pressure ratio (NPR) used were from 1.5 to 3, in steps of 0.5 and experiments were conducted for NPR 1.5, 2.0, 2.5 and 3.0. The geometrical parameter, the length to diameter ratio of the enlarged duct was varied from 10 to 1, and tests were conducted for L/D 10, 8, 6, 5, 4, 3, 2 and 1. When the micro jets were activated they are found to influence the base region, taking the base suction to considerably higher values compared to that for without control case for most of the cases. From the present study it is found that as the NPR increases, the effect on base pressure is marginal for NPRs up to 2.5; however, at NPR 3 there is a sudden decrease in the base pressure. Further, it is found that the micro jets are very effective in controlling the base pressure and the active control in the form of micro jets does not disturb the flow field in the duct, however, wall pressure becomes oscillatory at NPR 3.